(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19), an epidemic illness caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), affecting the lower respiratory tract. It may impact renal and hepatic function by causing a cytokine storm and inflammation. Although numerous studies on the effects of COVID-19 on people with diabetes Mellitus (DM) have been conducted across the globe, their conclusions have varied due to differences in study populations’ demographics, racial and ethnic composition, and geographic locations. Objective: To comprehend the effects of a severe COVID-19 infection on renal and hepatic function in patients with diabetes mellitus. Methods: This study was carried out at the Chemistry and Biochemistry Department of Al-Nahrain University in Baghdad, Iraq. A total of 100 participants with a severe case of COVID-19 were included in the study between February and April 2022. There was a total of 100 hospital admissions due to COVID-19; 50 of these patients had diabetes, while the other 50 did not. In both groups, serum urea, creatinine, glutamic-oxaloacetic ?transaminase (GOT) and glutamic-pyruvic ?transaminase (GPT) were mustered using ?appropriate methods.? Results: The median concentration of the DM patients’ group had significantly lower concentration of urea, creatinine, GOT and GPT than non-DM patient’s group. While all these parameters were significantly higher in COVID-19 patients than in controls. Conclusion: Diabetes (COVID-19 patients) exhibited lower levels of biochemical markers as compared to non-diabetic people. Patients with diabetes in COVID-19 take a range of drugs, including insulin injections. In severe circumstances, this medicine may disrupt biochemical markers in addition to the effects it has on renal and hepatic function from COVID-19. Keywords: COVID-19, diabetes Mellitus, urea, creatinine, GOT, and GPT. Citation: Yones MS, Alwasiti EA, Al-Qaseer AA, Nile AK. The Impact of severe COVID-19 infection on renal and liver markers (urea, creatinine, GOT, GPT) in diabetic patients. Iraqi JMS. 2023; 21(2): 237-244. doi: 10.22578/IJMS.21.2.11